Exploring Citizenship Unit I: Me, My Family, and My Friends! - John Rutledge; Joy C. Jordan; Dale Pracht (EDIS)
The 4-H Citizenship Project offers you the opportunity to help 4-H members relate all of their 4-H projects and experiences to the world around them. They will learn to care for and share with others through the skills and talents they’ve developed.